The Intersection of Islamic and Civil Law in Indonesian Will Legislation - Prana, Muhammad; Nurasiah, Nurasiah; Siregar, Ramadhan Syahmedi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
A will in Islamic law (wasiah) is a written or oral declaration made by a person (wasi) during their lifetime to regulate the distribution of their property after their death. The following are some important points about wills under Islamic law. A will in civil law, also known as a testament or probate, is a written instruction made by a person (testator) to arrange for the distribution of their property after their death. In practice, wills in Islamic law can provide individuals with the flexibility to organize a fraction of their estate according to personal wishes, albeit subject to the limitations set out by Sharia. In the context of civil law, will give individuals control over the distribution of their property after death and ensure that their wishes are respected. Wills can also help avoid inheritance disputes and provide legal certainty for heirs. The focus of this research is: First, how is the comparison of Islamic law with civil law in the regulation of wills in the State of Indonesia, second, how is the analysis of the perspective of the majority of people using the law in the application of wills? The model used in this research is qualitative, while the approach used is a literature study by analyzing the data obtained. The preliminary step in this research is to search for relevant literature data sources from various contexts by analyzing the findings and arguments from each source, as well as comparing and contrasting information to conclude. The results of this research show that there are similarities and differences between wills in Islamic law and civil law. The similarities can be seen in the validity of wills, the necessity to be written, and witnesses, and the differences can be seen in the limitations of inheritable property, cancellation and amendment of wills, the implementation of wills, disputes over wills, and the purpose of wills. The perspective of the majority of people in using the law related to the application of wills in Indonesia can be seen from the influence of culture and religion, legal rudeness and level of legal knowledge, legal practice in the field, trust and compliance, and involvement of legal professionals.